The fourth edition of the European Network for Health Technology Assessment Forum: highlights and outcomes. (22nd June 2020) - Tafuri, Giovanni; Bélorgey, Chantal; Favaretti, Carlo; Frénoy, Edith; Giorgio, Flora; Guardian, Marcus; Hebborn, Ansgar; Houÿez, François; Imbert, Jessica; Lacombe, Denis; Garcia, Jordi Llinares; Garrett, Zoe; et al.
Abstract : The European Network for Health Technology Assessment (EUnetHTA) organizes an annual Forum with stakeholders to receive feedback on its activities, processes, and outputs produced. The fourth edition of the EUnetHTA Forum brought together representatives of HTA bodies, patient organizations, healthcare professionals (HCPs), academia, payers, regulators, and industry. The aim of this paper is to provide an overview of the highlights presented at the 2019 EUnetHTA Forum, reporting the main items and themes discussed in the plenary panel and breakout sessions. The leading topic was the concept of unmet medical need seen from different stakeholders' perspectives. Breakout sessions covered the joint production of assessment reports and engagement with payers, patients, and HCPs. Synergies, pragmatism, and inclusiveness across Member States and stakeholders were emphasized as leading factors to put in place a collaboration that serves the interest of patients and public health in a truly European spirit.